An Evaluation of Holistic Sustainability Assessment Framework for Palm Oil Production in Malaysia - Biswas, Wahidul; Ing Lim, C. (MDPI AG, 2015)
Palm oil based biodiesel offers an alternative energy source that can reduce current dependence on conventional fossil fuels and may reduce greenhouse gas (GHG) emissions depending on the type of feedstock and processes used. In the Malaysian context, the palm oil industry not only provides high-yield, renewable feedstock to the world, it brings socio-economic development to the Malaysian rural community and contributes to the national income. However, the sustainability of palm oil remains controversial, due to deforestation, pollution and social conflicts associated with its production. Sustainability assessment is vital for the palm oil industry to identify weaknesses, improve its sustainability performance and improve consumer confidence. This paper proposes a holistic sustainability assessment framework for palm oil production with the aim to address the weaknesses of existing palm oil sustainability assessment methods. It identifies environmental, social and economic Headline Performance Indicators, Key Performance Indicators and their Performance Measures in crude palm oil production in a structured framework. Each quantitative/semi-quantitative performance measure is translated into Likert Scale of 1–5, where 3 is the threshold value, 5 is the ideal condition, and 1 is the worst case scenario. Calculation methods were established for the framework to provide quantitative assessment results. The framework was tested using a hypothetical example with data from existing studies. The results suggest that crude palm oil production in Malaysia is below the sustainability threshold. Evaluations of this sustainability assessment framework also demonstrate that it is a comprehensive assessment method for assessing sustainability of feedstock for biofuel production.